2017
DOI: 10.1021/acscatal.6b03682
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Nb2O5 as a Selective and Reusable Catalyst for Furfural Production from Xylose in Biphasic Water and Toluene

Abstract: Aqueous-phase dehydration of xylose into furfural was studied in the presence of amorphous Nb2O5 with water-compatible Brønsted and Lewis acid sites. Nb2O5 was determined as a more active and selective catalyst for xylose dehydration than typical homogeneous Brønsted and Lewis acid catalysts including HCl and Sc­(OTf)3, and Nb2O5 converted 93% of xylose with 48% selectivity toward furfural in water at 393 K. No significant loss of the original catalytic activity was observed after Na+-exchange treatment, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
85
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 45 publications
0
85
1
Order By: Relevance
“…We have previously reported that the conversion of glucose and xylose to HMF and furfural over Lewis acid sites on Nb 2 O 5 and TiO 2 surfaces is based on step‐wise dehydration via the formation of dicarbonyl compounds typically represented by 3‐deoxyglucosone . In the case of glucose conversion, the Lewis acid sites facilitated the subsequent dehydration of 3‐deoxyglucosone to yield HMF as a main product.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that the conversion of glucose and xylose to HMF and furfural over Lewis acid sites on Nb 2 O 5 and TiO 2 surfaces is based on step‐wise dehydration via the formation of dicarbonyl compounds typically represented by 3‐deoxyglucosone . In the case of glucose conversion, the Lewis acid sites facilitated the subsequent dehydration of 3‐deoxyglucosone to yield HMF as a main product.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies in the field use a reaction temperature of approximately 130°C. [21][22][23][24][25][26][27][28][29][30][31] We used simulations to explore the performance of a membrane reactor operating at that temperature. There was no difficulty performing the batch experiments without extraction and with liquidliquid extraction (LLE) at 130°C.…”
Section: Resultsmentioning
confidence: 99%
“…These reactors are typically operated at temperatures of 130-180°C. [21][22][23][24][25][26][27][28][29][30][31] Solvents include toluene, [21][22][23][24] methyl isobutyl ketone, [23][24][25][26] cyclopentylmethyl ether, [27][28][29] among others, and are typically used in organic : aqueous volumes ratios greater than 1 in order to increase furfural extraction. The furfural yield depends on solvent, catalyst, xylose loading, etc.…”
Section: Introductionmentioning
confidence: 99%
“…5–8), (3) dehydration reactions of alcohols and polyols (No. 9–16),, (4) nucleophilic substitution reactions of carboxylic acids (and their derivatives),, and (6) selective oxidation/dehydrogenation reactions …”
Section: Introductionmentioning
confidence: 99%
“…9), have led to the new research area Nb 2 O 5 ‐catalyzed dehydration of biomass‐derived polyols (No. 10–16) . The hitherto reported Nb 2 O 5 ‐catalyzed dehydrative transformations of polyols are concerned with the dehydration of glycerol to acrolein (No.…”
Section: Introductionmentioning
confidence: 99%